Dynamic modeling and motion analysis for a dual-buoyancy-driven full ocean depth glider - Wang, Shuxin; Li, Haozhang; Wang, Yanhui; Liu, Yuhong; Zhang, Hongwei; Yang, Shaoqiong (Ocean engineering, 2019)
This paper presents a dual-buoyancy-driven mechanism for Petrel-X, a full ocean depth glider, to adjust its buoyancy and pitch angle simultaneously. The proposed dynamic model is derived from the Newton-Euler formulation by integrating the influences of environmental parameters and change in displaced volume of the glider. The adaptive buoyancy adjustment and the subsequent motion performances are investigated. The adaptive buoyancy adjustment is realized by adopting the passive buoyancy compensation to maintain neutral buoyancy and using the dual-buoyancy-driven mechanism to adjust the buoyancy actively. The coefficient of deep contraction is defined to describe the ability of maintaining neutral buoyancy and determine the optimal quantity of the passive buoyancy compensators. With the proposed approach, the net buoyancy variation in the full ocean depth decreases by 70.8%. The motion is simulated based on the dynamic model. The simulation data are analyzed with the neural network trained by the Bayesian Regularization backpropagation algorithm to guide the parameter settings for the sea trials. In April 2018, the Petrel-X glider was deployed in the Mariana Trench, which dived down to 8213 m. The agreement between the simulation and experimental results confirms the feasibility of the proposed methods. •A dual-buoyancy-driven mechanism adjusts buoyancy and pitch angle simultaneously.•The dynamic model integrates changes in seawater parameters and the buoyancy.•Petrel-X glider is an innovative full ocean depth glider for deep ocean research.•The passive buoyancy compensation makes the glider maintain neutral buoyancy.•The net buoyancy variation in the full ocean depth range decreases by 70.8%.